Farmer perceptions toward the adoption of agroforestry practices: a case study of northwestern Ethiopia - Mulunesh Yayehrad Gashu; Demamu Mesfin; Tadsual Asfaw Dessie (Frontiers in Sustainable Food Systems)
IntroductionDespite several reports emphasizing the role of agroforestry in enhancing rural livelihoods, promoting sustainable development, protecting the environment, and supporting climate change mitigation and adaptation, little is known about rural households’ perceptions of the different benefits of agroforestry and the extent of adoption of its different agroforestry technologies, including contour farming with tree planting, alley cropping, woodlot and timber production, integration of fruits, nuts, medicinal trees, home gardens, fruits on farmland, boundary cropping, and live fences. Therefore, this study aimed to examine farmers’ perceptions and adoption of agroforestry practices as well as the factors influencing these actions in the Banja district of Northwestern Ethiopia.MethodsA cross-sectional research design was conducted in three kebeles of the Banja district, encompassing a sample of 340 households. The study employed a quantitative and qualitative approach, with multi-stage sampling technique results employed to select sample households using a binary logit model.Result and discussionsThe study found that 59% of respondents perceived agroforestry as advantageous, with 91.57, 75, and 60.5% recognizing its benefits for farm productivity, household income, and food security, respectively. The remaining 41% of sample households were not perceived. Approximately 56% of the respondents adopted different agroforestry practices, mainly live fences and taungya. The results of the binary logit model indicated that the adoption of agroforestry practices was influenced by factors such as sex, educational status, access to extension services, family size, soil fertility, farmland size, and slope of farmland. In contrast, age, distance to farmland, land tenure, livestock size, farm experience, and market distance were not significant. The study recommends that extension workers should strengthen rural education, improve extension services, focus on soil fertility through soil and water conservation practices, and ensure sustainability through regular monitoring, evaluation, and implementation of diverse agroforestry practices, thereby ensuring environmental sustainability and improving livelihoods at the household, community, and national levels.